Clinical effect and biological mechanism of exercise for rheumatoid arthritis: A mini review - Li, Zongpan; Wang, Xue-Qiang (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is a common systematic, chronic inflammatory, autoimmune, and polyarticular disease, causing a range of clinical manifestations, including joint swelling, redness, pain, stiffness, fatigue, decreased quality of life, progressive disability, cardiovascular problems, and other comorbidities. Strong evidence has shown that exercise therapy is effective for RA treatment in various clinical domains. Long-term exercise seems to decrease disease activity. However, the mechanism underlying the effectiveness of exercise in alleviating RA remains unclear. This review first summarized and highlighted the effectiveness of exercise in RA treatment. Then, we integrated current evidence and proposed biological mechanisms responsible for the potential effects of exercise on immune cells and immunity, inflammatory response, oxidative stress, and epigenetic expression on inflammatory factors and matrix metalloproteinases. However, a large body of evidence was obtained from the healthy population, animal studies, or participants with other diseases. We look forward to future studies that would further examine proposed biological mechanisms responsible for the effectiveness of exercise in alleviating RA